Evaluation of Internet channels and their impacts on Irish mobile operators' business models - Ademowo, Adewale (2013)
Ademowo, Adewale Adebayo Evaluation of Internet Channels and their impacts on Irish Mobile Operators' Business Models Jyväskylä: University of Jyväskylä, 2013, 108 p. Mobile Technology and Business (Major in Information Systems Science), Master's Thesis Supervisor: Luoma, Eetu